Organizacija združenih narodov in varstvo človekovih pravic - Roter, Petra (Teorija in praksa, 2016)
The paper aims to analyse the role of the United Nations (UN) in the area of international protection of human rights, in terms of both norm development (i.e. through international conventions) and the development of mechanisms for monitoring the implementation of norms. To achieve this goal, the paper applies a historical analysis. Special attention is paid to the significance of the Cold War as an obstacle to further development of the global human rights regime. The paper relies on extensive use of primary sources - human rights documents adopted by the UN over the period of seven decades. The paper ends by reflecting on further challenges for the UN in the field of international protection of human rights.
Keywords: Človekove pravice; Human rights; International law; mednarodne konvencije; Mednarodno pravo; Organizacija združenih narodov